Headspace generation coupled to gas chromatography–mass spectrometry for the automated determination and quantification of endogenous compounds in urine. Aldehydes as possible markers of oxidative stress - Antón, Ana Pérez; Ferreira, Ana María Casas; Pinto, Carmelo García; Cordero, Bernardo Moreno; Pavón, José Luis Pérez (Journal of Chromatography A, 2014)
•HS-PTV-GC–MS coupling for determination of five aldehydes in urine samples.•Minimization of sample manipulation and shortening of pre-treatment time.•Simplification due to no derivatization requirement.•External calibration for quantification of analytes in healthy subjects’ urine.•LODs obtained ranged between 0.04 and 0.08μg/L. A methodology for the determination of five aldehydes in urine has been developed based on the coupling of a headspace generation sampler with a gas chromatography–mass spectrometry system equipped with a programmed temperature vaporizer. This instrumental configuration minimizes sample manipulation and allows the determination of these compounds without the need for a derivatization step so that the methodology is largely shortened and simplified. An experimental design was carried out in order to optimize the headspace sampling. Sample matrix effect was eliminated by means of dilution of urine samples. The calibration models displayed good linearity (0.1–10μg/L) and their validity was checked using ANOVA, and it was observed that they did not exhibit any lack of fit. The LODs obtained ranged between 0.04 and 0.08μg/L and the LOQs between 0.12 and 0.24μg/L. The accuracy of the method was evaluated in terms of apparent recoveries which were between 86 and 120%. The method developed was applied to the analysis of 17 samples of urine from different subjects in order to quantify these endogenous compounds.